2018
DOI: 10.1177/1071100717746192
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tendoscopy in Treating Stage II Posterior Tibial Tendon Dysfunction

Abstract: Level IV, therapeutic study, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 69 publications
1
15
0
1
Order By: Relevance
“…Our case series reported an improvement in VAS scores for pain from 7 points at baseline (preoperative) to 1.27 points at 24 months. This notable difference is consistent with the findings of Bernasconi et al (17) , who reported an improvement in VAS mean scores from 7.9 to 3.5 points and found low complication rates after the procedure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our case series reported an improvement in VAS scores for pain from 7 points at baseline (preoperative) to 1.27 points at 24 months. This notable difference is consistent with the findings of Bernasconi et al (17) , who reported an improvement in VAS mean scores from 7.9 to 3.5 points and found low complication rates after the procedure.…”
Section: Discussionsupporting
confidence: 92%
“…Gianakos et al (19) , in a study assessing 12 patients (8 with stage I PTTD and 4 with stage II PTTD), showed that 75% of patients had good outcomes. Similarly, Bernasconi et al (17) reported 75% of positive outcomes among 16 patients with stage II PTTD. Positive outcomes were achieved in 90% of our series; moreover, of the 6 cases of PTTD, 4 were classified as stage I and two as stage IIa.…”
Section: Surgical Management Of Stage I Pttd Consisted Of Synovectomymentioning
confidence: 87%
“…The diagnosis of stage 2 PTTD is confirmed clinically and radiologically. Magnetic resonance imaging and ultrasonography are useful in detecting PTT lesions 12 . However, tendoscopy is more effective than magnetic resonance imaging for detection of a spring ligament tear 12, 14…”
Section: Techniquementioning
confidence: 99%
“…Endoscopic synovectomy has also been used in management of stage 2 PTTD and can allow for continued conservative therapy while avoiding more invasive surgery in most cases. 10 , 12 In contrast to stage 1 disease, calcaneal and medial column osteotomies may be needed in addition to the endoscopy with synovectomy. 10 Recently, a technique of endoscopically assisted PTT reconstruction has been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation